"All those Elvis-meets-golf-player looks": A corpus-assisted analysis of creative compounds in fashion blogging. (June 2016) - Crawford Camiciottoli, Belinda
Abstract: This paper offers a comprehensive analysis of compounds as creative forms of self-expression in a leading fashion blog (Style.com), where users engage in conversations about fashion. The aim was to determine to what extent and how compounds are used by fashion bloggers, with particular attention to creativity, and how this usage may be influenced by the online communicative context. Compounds are notoriously difficult to investigate due to their marked structural variation and inconsistent orthographic representation. However, thanks to a corpus-assisted approach, it was possible to first systematically identify compounds in the blog, and then analyze them in context to detect forms, patterning, functions and creative usage. Most compounds functioned as adjectives, in line with the descriptive and evaluative nature of fashion discourse. However, a high level of creativity was seen in compounds with uncommon structural components (e.g., verb+preposition as in go-to ), novel combinations (e.g., skull-embellished ), creative recycling of participial constituents (e.g., -inspired, -inducing ), and especially phrasal structures that trigger striking mental images (e.g., stripper-cum-S&M freak ). The study contributes to a better understanding of how bloggers use creative language to construct their identities as members of a distinctive and cohesive social community. Highlights: Corpus methods were used to analyze creative compounds in fashion blogging. Creativity emerged through uncommon structural components and novel patterning. Elaborate phrasal compounds that trigger striking mental images were distinctive. Creative compounds reflect self-identity as members of the online fashion community.